Analysis of Tensile Strength of Bamboo Fiber Composites Made by Hand Lay Up Manufacturing Method - Subianto, Nicki
One of the natural fiber that available much around us is bamboo. Bamboo has grow time a lot faster and cheaper prices than wood. If we make bamboo to be a composite, then the strength and resilience of this material will increase and therefore has more functionality. This study tested the tensile strength of bamboo fiber composite (modulus of elasticity and Ultimate Strength) with a variety form of fibers (fibers form a flat and sticks), analyzed the comparison with the tensile strength fibers and resins are used, and analyzed the failure mode occurs. Thin flat bamboo fiber composite has an average value of modulus elasticity 6.424 GPa and the ultimate strength of 97.5 MPa. Stick bamboo fiber composite has an average value of modulus elasticity 4.894 GPa and the ultimate strength of 39.37 MPa. All the test specimens failed due to shear stress. Epoxy resin has an average value of modulus elasticity 1.52 GPa and the ultimate strength of 17.51 MPa. Flat thin bamboo fiber has an average modulus elasticity 19.08 GPa and the ultimate strength of 245.6 MPa. Stick bamboo fiber has average value of modulus elasticity 34.78 GPa and the ultimate strength of 323.29 MPa.